Post-operative biliary stricture due to plexus amputation neuroma pericoledociano - Juambeltz, Carlos; Fernández, Gonzalo; Chiossoni, Marta; Vercelli, Jorge; Praderi, José; Beguiristain, Alberto; Praderi, Raúl (Cirugía del Uruguay, 1991)
Two patients who had undergone choledochotomy suffered from late stenosis of the main biliar viae (3 and 1 yhear la ter). Both were treated by stricture resection and hepatico-jejunal anastomosis. The histological study showed amputation neuromas in both cases. This rare lesion has been reported in very few cases in reference literature.